MENUMBUHKEMBANGKAN KESADARAN DAN KETERAMPILAN METAKOGNISI MAHASISWA JURUSAN BIOLOGI MELALUI PENERAPAN STRATEGI PBL DAN KOOPERATIF GI - Muhammad Danial (Bioedukasi Jurnal Pendidikan Biologi, 2010)
The teaching of the educational levels including at the university level is still emphasized on the aspect of cognitive ability. The emphasis on the aspect of empowering the metacognitive is not touched yet. As a matter of fact, there are some techniques of teaching that can be applied to empower their metacognitive ability such Problem-based Learning (PBL) and cooperative Group Investigation (GI) strategy applies. This study aims to explain the effect of PBL and cooperative GI strategy to the metacognition and this study use “Pretest-Posttest Nonequivalent Control Group Design”. This study indicates that students that learned with PBL and GI strategy have scores of metacognition from pretest to posttest higher than students that learned with conventional strategy. Based on the ANACOVA test showed that there were significance differences of students’ metacognition ability between the students who were thought through PBL strategy and the students who were thought through conventional and GI strategy. Kata kunci: PBL, kooperatif GI, metakognisi